Effect of Curing Modes on the Mechanical Properties of Commercial Dental Resin-Based Composites: Comparison between Different LEDs and Microwave Units - Vermudt, Alef; Kuga, Milton Carlos [UNESP]; Besegato, João Felipe [UNESP]; Oliveira, Eliane Cristina Gulin de [UNESP]; Leandrin, Thaís Piragine [UNESP]; Só, Marcus Vinicius Reis; Moraes, João Carlos Silos [UNESP]; Pereira, Jefferson Ricardo (MDPI, 2022)
Resin-based composites (RBCs) have transformed restorative dentistry and its procedures. However, the characteristics of RBCs have been modified over the years to enhance the physical and chemical properties of the materials. This context raises the need for studies that evaluate whether the properties of the RBCs that are commercially available are clinically adequate with different curing modes. This study aimed to evaluate the mechanical behavior of commercial RBCs after undergoing different curing modes. Twenty-three RBCs of different classes were evaluated. For curing the specimens, a microwave (BMS45, Brastemp) (for 3 min at 450 W) and three LED units were used: an Emitter A Fit (Schuster (second generation)) (light-curing for 15 s with an irradiance of 1250 mW/cm2), VALO (Ultradent (third generation)) (light-curing for 15 s with an irradiance of 1100 mW/cm2), and Emitter Now Duo (Schuster (second generation)) (light-curing for 15 s with an irradiance of 1100 mW/cm2). A total of 670 RBC specimens of 8 mm in diameter and 1 mm in depth were obtained. Afterward, a biaxial flexure strength test was performed until the failure of the specimens, using a universal testing machine set at a speed of 0.5 mm/min. The same specimens were subjected to infrared spectroscopy for evaluating the degree of conversion. Tukey’s test was used for multiple comparisons at a significance level of 5%. The light-curing mode did not affect the flexure strength of the RBCs (p > 0.05), but the type and shade of RBCs did so (p < 0.05). In conclusion, the type of RBC directly interferes with the mechanical behavior of the material. However, the curing modes within the same RBC did not change the mechanical properties.
Keywords: curing; degree of conversion; flexure strength; LED source; resin composites